Sealing ability of different Root-End filling Materials (Mustansiria Dental Journal, 2004)
This study evaluated the ability of mineral trioxide aggregate (MTA) ot seal the root end effectively. Forty-five single rooted, extracted human teeth were cleaned & shaped using a step back technique. The root-ends were resected, &a 3-mm deep root- end preparation was made. The teeth were random divided into three groups of 15 & filled with dental amalgam, super-EBA, or MTA, folowing immersion ni 1%methylene blue dye for 72hours, the roots were sectioned & the depth of dye penetration was evaluated by a stereomicroscope at X-10 magnification. The sealing effectiveness of the retrograde filling materials used ni this study was determined by their ability ot inhibit dye penetration. MTA cement provides a better seal than amalgam & EBA cement when used as retrograde filling, but the extrapolation of this result into a clinical practice may be questionable.